Bentuk, fungsi, dan makna budaya dalam cerita rakyat Asrah Batin di Kabupaten Grobogan - Rahayu, Eka Puspita; Werdiningsih, Yuli Kurniati; Sunarya, Sunarya (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2025)
The Asrah Batin tradition is a regional tradition that is still ongoing today. The Asrah Batin tradition is a social phenomenon that needs attention from the community. Therefore, it is necessary to examine to find out the form, function, and meaning of this tradition. The problems studied are related to the Asrah Batin tradition, namely (1) how is the form, function and meaning of the Asrah Batin tradition for the supporting community. The aims of this study are (1) to describe the form, function and meaning of the Asrah Batin tradition. The method used in this study is a qualitative descriptive method using a folklore approach. The results of the research are (1) The forms in the Asrah Batin tradition are divided into three stages, namely the preparation stage, the highlight of the event, and the closing event. In the preparation stage, the Gebyuk, Tuba, and Nyekar events were carried out. At the peak of the event there is a procession of sasrahan, panggih, wisuhan, reading of the history of Asrah Batin, Selametan (Kembul Bujana), Munggut, and srah-srahan. Meanwhile, the closing ceremony was performed with a tayub dance performance. (2) the functions of the existence of the Asrah Batin tradition for the supporting community are religious functions, educational functions, social and cultural functions, economic functions, and entertainment functions. (3) The symbolic meaning contained in the Asrah Batin tradition is the symbols in ubarampe. The symbols contained in ubarampe generally contain the meaning of hope and prayer to God, mutual forgiveness, advice to maintain kinship, maintain self-purity and ask for safety and blessings. The conclusions in this study are (1) The forms in the Asrah Batin tradition are divided into three stages, namely the preparation stage, the highlight of the event, and the closing event. (2) the functions of the existence of the Asrah Batin tradition for the supporting community are religious functions, educational functions, social and cultural functions, economic functions, and entertainment functions. (3) the meaning of the Asrah Batin tradition is in the form of symbolic meaning contained in the ubarampe used in the Asrah Batin tradition. The segatumpeng symbol has the meaning of three stages of human life, namely starting from still in the womb, life in the world, and death. These three stages must always be remembered by humans, because everything will return to Allah, ingkung means human submission to God and asking for forgiveness and being given safety, wedhak boreh ix has the meaning that people who hold salvation or ceremonial rituals are given safety and blessings.